Cross-Cultural Communication to Support the Education of Indonesian Migrant Children: An Ethnographic Study at the AMI Tutoring Center in Penang, Malaysia - Alifa Salma Musyaffa; Oki Cahyo Nugroho; Niken Lestarini; Krisna Megantari (Universitas Ahmad Dahlan, 2025)
Increasing numbers of undocumented Indonesian migrant children in Malaysia face limited access to formal schooling and must navigate multilingual, multicultural environments that shape their learning experiences. While previous studies focus on legal and administrative barriers, the role of cross-cultural communication in non-formal education remains understudied. This research examines how communication practices support inclusive education at the AMI Penang Guidance Center. The study aims to explore how migrant children manage linguistic and cultural differences in daily learning and how educators adapt their communication to meet diverse needs. Using an ethnographic approach, data were collected through participant observation and semi-structured interviews with six children (ages 9–11) and educators at the center. Analysis followed thematic coding and was interpreted using Hurn and Tomalin’s cross-cultural communication and STAR (Stop, Think, Assess, Respond) frameworks. Findings show that children frequently experience confusion, hesitation, and identity negotiation when switching between Indonesian, Malay, and their mother tongues. Educators interpret these behaviors through cultural rather than purely linguistic lenses and respond with bilingual scaffolding, culturally familiar materials, emotional support, and flexible teaching strategies. These practices enhance students’ confidence, communication skills, and sense of belonging. The study contributes theoretically by positioning cross-cultural communication as a core dimension of inclusive education in transnational settings. Practically, it offers insights for designing culturally responsive non-formal education for undocumented migrant children.